SOCIAL DISTANCING UPAYA PENCEGAHAN PENYEBARAN COVID-19 PERSPEKTIF MAQASHID AL-SYARIAH - zezen zainul ali (Postgraduate State Islamic Institute (IAIN) Metro, 2020)
Pandemic COVID-19 has shocked the world the number of victims of this virus has also reached a high number, even in Indonesia the spread of this virus has spread over time, meeting the fallen victims saved, keep moving to prevent this virus, one can find by appealing to the public to do social ditance that is spending distance with others and avoiding the crowd, to asking the government to issue such as working from home, eliminating activities that involve many people to spend religious activities, this is a lot of pros and cons in the community, of course, the Muslim community, the reason is that social appeals are reinforced, there are no legal rules in Islam either in the Koran and Hadith. This study uses literature data that is analyzed qualitatively. and will discuss the law of the social using maslahah theory which maslahat is the goal of Islamic law (maqshid al-shariah).